2023
DOI: 10.1371/journal.pgph.0000790
|View full text |Cite
|
Sign up to set email alerts
|

A changing landscape: Tracking and analysis of the international HDV epidemiology 1999–2020

Abstract: The international epidemiology of Hepatitis Delta Virus (HDV) is challenging to accurately estimate due to limited active surveillance for this rare infectious disease. Prior HDV epidemiological studies have relied on meta-analysis of aggregated and static datasets. These limitations restrict the capacity to actively detect low-level and/or geographically dispersed changes in the incidence of HDV diagnoses. This study was designed to provide a resource to track and analyze the international HDV epidemiology. D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This study underscores the need for clearer guidelines on HDV testing and reporting across the United States and territories. With only 55% of states and territories requiring the reporting of HDV-positive test results and the noted changes in HDV epidemiology [ 10 , 11 ], it is crucial that an HDV case definition be developed to support consistent testing and improved tracking of HDV epidemiology. Furthermore, this approach would assist the CSTE in evaluating whether to recommend the inclusion of HDV in the CDC list of notifiable infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study underscores the need for clearer guidelines on HDV testing and reporting across the United States and territories. With only 55% of states and territories requiring the reporting of HDV-positive test results and the noted changes in HDV epidemiology [ 10 , 11 ], it is crucial that an HDV case definition be developed to support consistent testing and improved tracking of HDV epidemiology. Furthermore, this approach would assist the CSTE in evaluating whether to recommend the inclusion of HDV in the CDC list of notifiable infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on HDV epidemiology in the United States have echoed the limited testing of HDV in the HBV patient population [ 7 , 12 ]. Fallon et al evaluated international HDV epidemiology and reported significant structural breaks of unknown origin in HDV epidemiology [ 11 ]. These studies emphasize the need for increased surveillance of HDV.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of HDV epidemiology in the United States have echoed the limited testing of HDV in the HBV patient population 7,10 . Fallon et al evaluated international HDV epidemiology and reported significant structural breaks of unknown origin in HDV epidemiology 11 . These studies emphasize the need for increased surveillance of HDV.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, HDV infection has received renewed attention worldwide, likely due to the WHO’s global viral hepatitis strategy, which aims to reduce new hepatitis infections by 90% by 2030, and the recent development of HDV-specific antiviral treatments [ 8 , 10 ]. Nevertheless, the regional, national, and global epidemiology of HDV remains poorly documented, although recent reports have suggested changing patterns [ 13 , 23 ]. Differences between selective and non-representative study populations, the often-limited number of samples included in studies, and the limited availability and standardization of the anti-HDV and HDV-RNA tests used can lead to major discrepancies in data that contribute to the global uncertainty around HDV prevalence [ 13 ].…”
Section: Discussionmentioning
confidence: 99%